Modern talking: Sufi socio-political discourse. Issue 2 (4th May 2018) - Milani, Milad; Adrahtas, Vassilis
Abstract: This article shares the findings of a socio-political discourse analysis of modern Sufism. The study is conducted from the multi-disciplinary perspective of studies in religion, and is based on the assessment of one-on-one qualitative interviews about the approach of three prominent world Sufi orders—the Chishti, Naqshbandi, and Nimatullahi—to society and politics. The case studies present a new interpretation of modern Sufi religious and political practice, which is then formulated into a working typology as a contribution towards the categorisation of Sufi socio-political disposition.